2017
DOI: 10.1002/cyto.a.23100
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative phase microscopy spatial signatures of cancer cells

Abstract: We present cytometric classification of live healthy and cancerous cells by using the spatial morphological and textural information found in the label-free quantitative phase images of the cells. We compare both healthy cells to primary tumor cells and primary tumor cells to metastatic cancer cells, where tumor biopsies and normal tissues were isolated from the same individuals. To mimic analysis of liquid biopsies by flow cytometry, the cells were imaged while unattached to the substrate. We used low-coheren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 76 publications
3
85
0
Order By: Relevance
“…In the case of building a model for clinical use, this means that each model must be possible to train on samples from one set of patients with known cancer types, while still retaining its classification accuracy on samples from other patients with unknown diagnosis. Achieving this robustness is crucial for any use of machine learning outside of the lab, and although several studies have shown the potential of various classification approaches to distinguish between cells of known types when trained on cells from the same individual [54] or on known cell lines [51], few studies so far have explicitly addressed this problem. Changes detected by image analysis were already visible on day 1 for 0.25 µM etoposide, whereas effects on viability, as detected with spectrophotometry assays, were detected only on day 3 for 5 µM etoposide concentration, leading to the conclusion that the morphological changes observed occur before and at lower concentrations than the reduction seen in cell metabolic activity or viability assays [51].…”
Section: Automated Analysis and Qpimentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of building a model for clinical use, this means that each model must be possible to train on samples from one set of patients with known cancer types, while still retaining its classification accuracy on samples from other patients with unknown diagnosis. Achieving this robustness is crucial for any use of machine learning outside of the lab, and although several studies have shown the potential of various classification approaches to distinguish between cells of known types when trained on cells from the same individual [54] or on known cell lines [51], few studies so far have explicitly addressed this problem. Changes detected by image analysis were already visible on day 1 for 0.25 µM etoposide, whereas effects on viability, as detected with spectrophotometry assays, were detected only on day 3 for 5 µM etoposide concentration, leading to the conclusion that the morphological changes observed occur before and at lower concentrations than the reduction seen in cell metabolic activity or viability assays [51].…”
Section: Automated Analysis and Qpimentioning
confidence: 99%
“…Moreover, Roitshtain et al used a low-coherence off-axis interferometric phase microscopy setup, which allows a single-exposure acquisition mode, and thus is suitable for quantitative imaging of dynamic cells during flow. After acquisition, the optical path delay maps of the cells were extracted and then used to calculate 15 parameters derived from the cellular 3D morphology and texture [54]. In a very recent study, activated macrophages were analyzed and information of both cellular morphology and molecular content were collected with the help of the combination of Quantitative Phase Microscopy (QPM), Raman spectroscopy, and auto fluorescence imaging [101].…”
Section: Automated Analysis and Qpimentioning
confidence: 99%
“…Recently, several approaches for quantitative phase imaging (QPI) have been developed for live-imaging of cancer cells in culture (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). As a label-free imaging technology that is non-cytotoxic even with prolonged exposure, QPI is a noninvasive method for single cell analysis of adherent cell behavior.…”
mentioning
confidence: 99%
“…Note that because the refractive index of a sperm cell is not homogenous, one cannot extract the refractive index directly from the OPD measurement. In addition, the quantitative phase maps produced by IPM have been shown in the past to be an excellent source of quantitative data for the application of machine learning techniques (10)(11)(12)(13). Furthermore, new parameters such as the dry mass of the cells and cellular compartments can now be derived (9).…”
mentioning
confidence: 99%